ASSESSMENT OF THE THERMAL CONDITION ELECTRIC POWER EQUIPMENT IN PROCESS INDUSTRY BY THE METHOD THERMOGRAPHY - Božo Ilić; Živoslav Adamović; Branko Savić; Nenad Stanković (Journal of Engineering & Processing Management, 2012)
During the operation of power equipment in the process industry failure can occur, which if not timely detected and corrected, could lead to major failures and disasters, and a time to unplanned downtime of entire production lines, which can lead to high costs, environmental damage and endanger the safety of workers is therefore within the program of preventive maintenance performed thermographic testing of power equipment. The aim of this is that propose new approach to determine defect of the method of thermography, which is based on determining the method, direction and direction of propagation of heat and temperature profile analysis. This approach allows to prove that the places are not always overheat and malfunction place. Results obtained with this approach are verified by results obtained using UI electrical transient measurements of electrical resistance of joints.
Keywords: thermal testing; electrical power equipment; assessment of thermal conditions; heat transfer; places of overheating